Determinan Kepatuhan Siswa terhadap Protokol Kesehatan Selama Pembelajaran Tatap Muka (PTM) - Amalia Ninggar; Ayun Sriatmi; Rani Tiyas Budiyanti (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Boyolali Sub-Regency had the highest total Covid-19 cases that was reported by Boyolali District Health Office on February 2022. The limited face-to-face learning / PTM in Boyolali Regency has been implemented on January 2022 with requirement of strict health protocols. The purposes of the study is to determine the affecting factors of students compliance in the application of health protocols during the limited face -to-face learning in Boyolali Sub-Regency. Quantitative research method with a cross-sectional approach. The total number of respondents were 359 students in SD/ MI, SMP / MTs, SMA / SMK and MA who determined by proportional sampling technique. Data were analyzed by frequency distribution and simple liniear regression.The percentage of respondents with high compliance is higher (53.5%) than respondents with low compliance (46.5%).The affecting factors were age, level of education,knowledge, infrastructure supervision of school and community members, school support, friends support, and family support which has (p-value <0,005).The factors that didn’t affect was gender (p>0,005). The school should empower school health center role. It was done by involving the students checking the application of health protocols. The education office can make a pocket book containing health protocol rules during the limited face -to-face learning which can be a guide for family. The dostrict health office should socialization to community that they can also monitor health protocols during the limited face -to-face learning